Memórias de Quem Tem Muito a Contar: Os Protagonistas e a História da Educação do Tabuleiro do Norte-Ce - Moura, Maria Lenúcia de (2006)
Leaving of the understanding of that history is made by all the agents who are involved in its dynamics are that I decided to tell the history of the education of the Tabuleiro do Norte city, and like this I was based on the look of its protagonists. Men and women who suffering to the determination from the northeast barren land and the limitation of the distances had occupied in thinking about education and the development of this city. As focus of this research, I searched centered verbal history in the narrative. For effect of the empirical research, I valued the social actor’s memory involved with the construction of the education of the city, between the years of 1958 and 1970; the 12 first years of emancipation politics of the city. The contribution of the social actors who had been involved directly in the process of development of the education of the city made possible the knowledge of the Tabuleiro do Norte’s. History seen under the look of the on personages to the educative phenomenon. The narratives of the social actors had talked about the conceptions, the participation and the consolidation of the school education in the city.The conception of the interviewed is pautada in the reverence to some of the anpporter of this history, who had been founding of the society educator of the Tabuleiro do Norte, responsible for the opening of classrooms of the midlle and high in this context, the interviewed teachers – first contractec – do not recognize themselves as protagonists of this history, must as that they demonstrate in its stories an anguish due to tack of recognition and respect their profession for long time. About the participation, the Tabuleiro do Norte population, of beginning, pay its education with donations. The organization of the Society Educator was the solution found for the community to take the school its children, since the governmental indifference with the Northeasr of the country was and is felt mainly in the interior of the States. Consisting as fomentadora of the education, the Society Educator of the Tabuleiro do Norte implement with the CNEC the high school, inexistent until then. The consolidation of the tabuleirense education was based in the private one, as much in that says about to the Society Educator, of the CNEC, as well as in the restrictec access to this was not easy, due to the distance, the material, the fardamento, the books, the contribution/donation – as for the high school – becase obstable that many did not began to transpose it. However, the Tabuleiro do Norte education was fruit of its people, men and women who worked so hard and that for apart trom the determinative ones of the time they were moved by the search of the knowledge